IS THE CATHOLIC CHURCH A SAFE SPACE FOR RELIGIOUS SISTERS? CHARTING THE AFRICAN TERRAIN USING THREE CASE STUDIES - Eze, Chika (Scriptura, 2013)
The Congregation for the Doctrine of the Faith from the Vatican asked the Leadership Conference of Women Religious in the US on 18 April 2012 to revise and place itself under the control of an archbishop.1 To date, there have been unsolicited visitations from the Vatican to the same religious women in the US from 2009-2011.2 These events are examples of de facto gender-based discrimination within the Catholic Church, which stultify religious sisters by the Church’s hierarchies, and prompt the question: ‘Is the Catholic Church a safe space for religious sisters?’This article uses a historical review to trace the trajectory of religious sisters in the Catholic Church across the ages to the present, in an attempt to analyze how sisters have been/are being constructed in the Church. Using feminist anthropology, the article analyzes various Church documents which show how women’s identities have been constructed. The analysis includes examining how the sisters also construct ‘who they are’ in the different eras of the Church’s life. In addition, profiles of three African religious sisters are used as case studies to argue that through personal agency and education, sisters have negotiated and constructed the Church’s space into safe space.